Versatile tape-drive target for high-repetition-rate laser-driven proton acceleration. (21st March 2023) - Xu, N.; Streeter, M. J. V.; Ettlinger, O. C.; Ahmed, H.; Astbury, S.; Borghesi, M.; Bourgeois, N.; Curry, C. B.; Dann, S. J. D.; Dover, N. P.; Dzelzainis, T.; Istokskaia, V.; et al.
Abstract: We present the development and characterization of a high-stability, multi-material, multi-thickness tape-drive target for laser-driven acceleration at repetition rates of up to 100 Hz. The tape surface position was measured to be stable on the sub-micrometre scale, compatible with the high-numerical aperture focusing geometries required to achieve relativistic intensity interactions with the pulse energy available in current multi-Hz and near-future higher repetition-rate lasers ( $>$ kHz). Long-term drift was characterized at 100 Hz demonstrating suitability for operation over extended periods. The target was continuously operated at up to 5 Hz in a recent experiment for 70, 000 shots without intervention by the experimental team, with the exception of tape replacement, producing the largest data-set of relativistically intense laser–solid foil measurements to date. This tape drive provides robust targetry for the generation and study of high-repetition-rate ion beams using next-generation high-power laser systems, also enabling wider applications of laser-driven proton sources.